Complete genome sequence of Streptococcus agalactiae strain GBS85147 serotype of type Ia isolated from human oropharynx. Issue 1 (December 2016) - de Aguiar, Edgar; Mariano, Diego; Viana, Marcus; Benevides, Leandro; de Souza Rocha, Flávia; de Castro Oliveira, Letícia; Pereira, Felipe; Dorella, Fernanda; Leal, Carlos; de Carvalho, Alex; Santos, Gabriela; Mattos-Guaraldi, Ana; et al.
Abstract Streptococcus agalactiae, also referred to as Group BStreptococcus, is a frequent resident of the rectovaginal tract in humans, and a major cause of neonatal infection. The pathogen can also infect adults with underlying disease, particularly the elderly and immunocompromised ones. In addition, S. agalactiae is a known fish pathogen, which compromises food safety and represents a zoonotic hazard. This study provides valuable structural, functional and evolutionary genomic information of a humanS. agalactiae serotype Ia (ST-103) GBS85147 strain isolated from the oropharynx of an adult patient from Rio de Janeiro, thereby representing the first human isolate in Brazil. We used the Ion Torrent PGM platform with the 200 bp fragment library sequencing kit. The sequencing generated 578, 082, 183 bp, distributed among 2, 973, 022 reads, resulting in an approximately 246-fold mean coverage depth and was assembled using the Mira Assembler v3.9.18. TheS. agalactiae strain GBS85147 comprises of a circular chromosome with a final genome length of 1, 996, 151 bp containing 1, 915 protein-coding genes, 18 rRNA, 63 tRNA, 2 pseudogenes and a G + C content of 35.48 %.